Measles resurgence in Brazil: analysis of the 2019 epidemic in the state of São Paulo - Cristina Makarenko; Alexandre San Pedro; Natalia Santana Paiva; Jefferson Pereira Caldas dos Santos; Roberto de Andrade Medronho; Gerusa Gibson (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To analyze the epidemiological profile of cases and the pattern of spatial diffusion of the largest measles epidemic in Brazil that occurred in the post-elimination period in the state of São Paulo. METHOD A cross-sectional study based on confirmed measles cases in 2019. Bivariate analysis was performed for socioeconomic, clinical, and epidemiological variables, according to prior vaccination and hospitalization, combined with an analysis of spatial diffusion of cases using the Inverse Distance Weighting (IDW) method. RESULTS Of the 15,598 confirmed cases, 2,039 were hospitalized and 17 progressed to death. The epidemic peak occurred in epidemiological week 33, after confirmation of the first case, in the epidemiological week 6. Most cases were male (52.1%), aged between 18 and 29 years (38.7%), identified as whites (70%). Young adults (39.7%) and children under five years (32.8%) were the most affected age groups. A higher proportion of previous vaccination was observed in whites as compared to Blacks, browns, yellows and indigenous people (p < 0.001), as well as in the most educated group compared to the other categories (p < 0.001). The risk of hospitalization was higher in children than in the older age group (RI = 2.19; 95%CI: 1.66-2.88), as well as in the unvaccinated than in the vaccinated (RI = 1.59; 95%CI: 1.45-1.75). The pattern of diffusion by contiguity combined with diffusion by relocation followed the urban hierarchy of the main cities' regions of influence. CONCLUSION In addition to routine vaccination in children, the findings indicate the need for immunization campaigns for young adults. In addition, studies that seek to investigate the occurrence of clusters of vulnerable populations, prone to lower vaccination coverage, are essential to broaden the understanding of the dynamics of transmission and, thus, reorienting control strategies that ensure disease elimination.